ASEANSPHERE - Universitas Ciputra international field trip programme to UiTM Pulau Pinang Branch 24 November 2023 / Suria Sulaiman … [et al.] - Sulaiman, Suria; Azmi, Azila; Mohd Azhari, Nor Khadijah; Abdul Wahab, Mohd Faisal; Mazlan, Nor Hafizah (UiTM Global @ Office of International Affairs, 2024)
In today's globalised world, the value of international experiences for university students cannot be underestimated. Not only do these experiences broaden students' horizons and expose them to diverse cultures, but they also foster personal growth, enhance academic learning, and equip students with valuable skills for the workforce. Universities are increasingly recognising the importance of experiential learning activities, such as field trips, in preparing their students for real-world challenges.